Authority Dispute Between State Institutions Whose Authorities from Regulations Below the 1945 Constitution: Sengketa Kewenangan Antarlembaga Negara yang Kewenangannya didasari Peraturan Perundang-undangan di bawah Undang-Undang Dasar 1945 - Saifulloh, Moh. Roziq; Riska Answendy, Putri (Jurnal Konstitusi, 2023)
The dispute over authority between state institutions whose authorities are based on regulations under the 1945 Constitution cannot be resolved through a decision (beschikking), considering that matters involving overlapping authority that has been included in the regulations (regelling) and will remain in effect unless one of the matters has been annulled. This research aims to elaborate the pattern of power restriction on state institutions and find out the resolution of authority disputes between state institutions whose authority is based on regulations under the 1945 Constitution. This research is a legal argumentation using a normative research approach. The results of the research show that each state institution obtains authority by attribution, which originates from the 1945 Constitution or from regulations under the 1945 Constitution. The annulment of material containing authority that is sourced from the regulations under the 1945 Constitution can only be carried out through a material test (judicial review) by the judiciary, namely the Supreme Court.